Introduction. Islamicate Lucknow Today: Historical Legacy and Urban Aspirations - Raphael Susewind; Christopher B. Taylor (South Asia Multidisciplinary Academic Journal)
Lucknow, a city once dominated by Shi’a nawab rulers, is now known for elites’ nostalgia for Islamicate pasts and masses seeking better futures. This special issue builds interdisciplinary dialogue about a city overwhelmingly represented in historical accounts and emplaces Lucknow within recent investigation of urban India in which the city of nawabs is largely absent. Focusing on the old city of Lucknow where Muslims still demographically predominate, our introduction blends ethnographic exploration of cultural memory with new statistical data on the old city’s changing population, socioeconomic ‘backwardness,’ and segregation. We frame Lucknow’s Islamicate old city in contemporary times as a place where north India’s beleaguered Muslim minority negotiates between their remembered cosmopolitan past and a present burdened by structural violence and communal riots—blending (rather than choosing between) modernity and tradition, cosmopolitanism and provinciality, melancholia and aspirations, history and future.